2006
DOI: 10.1152/ajpheart.00333.2006
|View full text |Cite
|
Sign up to set email alerts
|

ENaC proteins contribute to VSMC migration

Abstract: Vascular smooth muscle cell (VSMC) migration plays a key role in tissue repair after arterial wall injury. VSMC migration requires integration of chemical and mechanical signaling mechanisms. Recently, we showed that epithelial Na(+) channel (ENaC) proteins are expressed in VSMCs and that ENaC inhibition abolishes pressure-induced constriction in isolated artery segments. However, whether ENaC proteins play a role in VSMC migration is unknown. The goal of this study was to determine whether ENaC molecules are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 60 publications
4
52
2
Order By: Relevance
“…Previous studies have shown that VSMC migration, from the media into the intima, plays a significant role following arterial injury, and blocking VSMC migration can reduce the neointimal lesion size (Rutherford et al, 1997;Slepian et al, 1998). A role for DEG/ ENaC/ASIC proteins in cellular migration has been suggested in recent reports (Chifflet et al, 2005;Grifoni et al, 2006;Vila-Carriles et al, 2006). Our previous study showed that DEG/ ENaC/ASIC pharmacological inhibition with amiloride and its analog benzamil inhibit VSMC migration.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies have shown that VSMC migration, from the media into the intima, plays a significant role following arterial injury, and blocking VSMC migration can reduce the neointimal lesion size (Rutherford et al, 1997;Slepian et al, 1998). A role for DEG/ ENaC/ASIC proteins in cellular migration has been suggested in recent reports (Chifflet et al, 2005;Grifoni et al, 2006;Vila-Carriles et al, 2006). Our previous study showed that DEG/ ENaC/ASIC pharmacological inhibition with amiloride and its analog benzamil inhibit VSMC migration.…”
Section: Discussionmentioning
confidence: 93%
“…We have used this approach previously to silence ENaC/ASIC expression Grifoni et al, 2006;Jernigan and Drummond, 2006). For migration assays, VSMCs were plated and allowed to grow to 90% confluence before transfection with siRNA molecules.…”
Section: Sirnamentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been suggested that in addition ENaC plays an important role in wound healing (33,34) and proliferation (35). Both ASIC and ENaC channels contribute to migration of vascular smooth muscle cells (36,37), although in neither case are the underlying mechanisms well understood.…”
Section: Discussionmentioning
confidence: 99%